Estimation of leakage current level on the transformer bushing using regression technique - Ahmad A.S.; Ghosh P.S.; Aljunid S.A.K.; Ahmad S. (2023)
System reliability requires monitoring of contamination on insulators surfaces especially near the coastal areas, and to take a convenient action when possible flashovers due to salt contamination may occur. The peak value of leakage current is one of the most widely used methods for this monitoring. Regression technique has been implemented successfully to estimate the value of the leakage current on a high voltage outdoor transformer bushing when the meteorological conditions are known and a mathematical model has been developed. The effect of the meteorological conditions such as humidity, pressure, temperature, wind speed and rainfall on the leakage current has been studied. The model is tested and good result of estimation has been found.